KOMPARASI FEMINISME PADA PUISI WENI SURYANDARI DAN RUPI KAUR - Faridah, Siti; Hartati, Dian (Universitas Hamzanwadi, 2022)
The purpose of this study is to describe a comparison of feminist views on two poems by Indonesian poets and Indian poets. The poems compared by the researchers include the title